A review on classification of trains for evaluate the railway network capacity of various speed trains. Issue 1 (1st October 2022) - Mittal, Manoj; Chaturvedi, Anand Kishore
Abstract : Railway is a very complicated decision making sector in a realistic way with numbers of constraints. Several thousands of trains are running over thousands of kilometers. The aim of this paper is to measure the rail network capacity by efficient utilization of existing resources of railway network by analytical model. In this model headway is reduced for variable speed trains so that track blocking time and track running time will be reduced. A case study of 14 sections with 5 corridors have analyzed by CIPLEX solver to develop the generic solution for optimizing rail network capacity to solve real problem. These models are useful in planning phase and can evaluate the entire network of railway.